Social Media as a Learning Space for Rethinking History Education among Digital Natives in Indonesia - Marwan Marwan; Abdul Hakim; Farida Febrianti; Eka Ariaty B (ANTHOR: Education and Learning Journal, 2026)
This study examines how social media functions as a learning space for rethinking history education among digital-native students in Indonesian senior high schools. Responding to the shift from textbook-centered learning to digitally mediated historical engagement, this study employed a qualitative case study approach involving 30 students and 12 history teachers from six senior high schools in South Sulawesi, Indonesia. Data were collected through semi-structured interviews, classroom observations, and document analysis, then analyzed using thematic analysis. The findings reveal four major themes: social media as an entry point to historical engagement, critical negotiation of digital historical narratives, participatory historical meaning-making, and tensions in social media-based history learning. Platforms such as YouTube, TikTok, Instagram, and WhatsApp increased students’ interest by presenting historical content in visual, multimodal, and familiar formats. However, students initially tended to judge credibility based on popularity indicators such as likes, views, and comments. Teacher mediation was therefore crucial in guiding students to evaluate sources, compare perspectives, contextualize historical events, and produce evidence-based digital narratives. The study concludes that social media can enrich history education when integrated with critical digital literacy and historical inquiry. Rather than replacing textbooks or teacher explanation, social media should function as a bridge between students’ everyday digital culture and the disciplinary practices of history learning.